Antibacterial and antifungal activity from extracts of Venezuelan marine algae - Ríos, Nurby (2009)
This study assessed the antibacterial and antifungal properties of 33 extracts (ethanol, dichloromethane, hexane) from 11 species of marine algae collected in the villages of San Juan de Los Cayos and Chichiriviche, Estado Falcon, Venezuela. The antibiotics and antifungal activity of extracts was evaluated by the appearance of halos of inhibition against gram-positive bacteria (Staphylococcus aureus), Gram negative (Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli) and the fungus Candida albicans. Of the 33 tested extracts showed antibacterial activity only 17 (5 with ethanol, 6 and 6 with dichloromethane-hexane), resulting assets compared to 14 species Gram(-) and 4 against the kind Gram(+). The algae species that showed antibacterial activity were: Acanthophora sp., Bryothamnion triquetrum, Gracilaria sp., Gelidium sp., Caulerpa mexicana, Caulerpa sp., Caulerpa spp., Halimeda incrassata, Ulva sp., Codium decorticatum, Sargassum sp.. None of the tested extracts from algae introduced antifungal activity on Candida albicans. The findings suggest that the algae on the west coast in Venezuela have bioactive compounds with antibacterial activity.